KORELASI ANTARA MOTIVASI BELAJAR DAN HASIL BELAJAR PEMBELAJARAN TEMATIK INTEGRATIF SISWA KELAS IV SD NEGERI 1 SAMBI BOYOLALI - Intan Rahmawati, Aris Budi Utami (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
Background of this study is the result of observation which indicate that the low level of learning?é?á outcome of the fourth students at SD Negeri 1 Sambi Boyolali on tematik integratif learning. The puposes of this study are to find out the correlation between motivation learning and learning outcome of the fourth students on tematik integratif learning at SD Negeri 1 Sambi Boyolali in academic year 2014/2015.Type of this study is an experimental quantitative method and the method which used by the writer is correlational. The population of` this study is the fourth grade students of SD Negeri 1 Sambi Boyolali. The sample which took by the writer in this study is the fourth students who the total number is 27 who consist of 10 male students and 17 female students. The writer got the sample by non probability sampling technique, especially the writer used by sampling jenuh. Hypothesis test used by correlation product moment analysis.Based on the result of the data analyses, there were positive colerration and significant between motivation learning and learning outcome on tematik integratif learning of the fourth students at SD Negeri 1 Sambi Boyolali.The result can be indicated in the rhitung value = 0,712 which compared by rtabel product moment with (dk) = N ?óÔé¼ÔÇ£ 1 =27 ?óÔé¼ÔÇ£ 1 =26, with standard significant 5% where rtabelvalue = 0,388. Thus rhitungvalue > rtabel value (0,712 > 0,388). The matter of motivation learning which influence learning outcome on tematik integratif learning of the fourth grade at SD Negeri 1 Sambi Boyolali is 50,69%. Meanwhile 49,31% learning outcome influenced by other factors.